Relationship of aerobic and neuromuscular indexes with specific actions in judo - Detanico, D.; Dal Pupo, J.; Franchini, E.; Giovana dos Santos, S. (Science & Sports, 2012)
Objective: The aim of this study was to verify the relationship of aerobic and neuromuscular indexes with specific situations in judo. Method: Eighteen male judokas took part in the study. The following assessments were performed: vertical jump (CMJ) on a force platform; Special Judo Fitness Test (SJFT) to obtain the number of throws and percentage of the maximal heart rate (%HRmax) one minute after the test; match simulation to obtain the peak blood lactate (LACmax) and the percentage of the blood lactate removal (BLR); incremental test to obtain the velocity at the anaerobic threshold (vAT) and peak velocity (PV) reached in the test. Results: A significant correlation was observed between the number of throws in the SJFT, the vAT (r = 0.60; P < 0.01), PV (r = 0.70; P < 0.01) and CMJ (r = 0.74; P < 0.01). A significant inverse correlation was found between the LACmax and vAT (r = -0.59; P = 0.01). Conclusions: It can be concluded that the performance in the SJFT was determined by the aerobic capacity and power and the muscle power. Athletes with greater aerobic ability (vAT) presented lower blood lactate accumulation after the match.